Synthesis and characterisation of magnetic-luminescent composite colloidal nanostructures. (2nd December 2009) - Roullier, V.; Marchi-Artzner, V.; Cador, O.; Dorson, F.; Aubert, T.; Cordier, S.; Molard, Y.; Grasset, F.; Mornet, S.; Haneda, H.
In this communication, we report a review of our works on luminescent and magnetic bifunctional structures in the nanoscale range. The synthesis and characterisation of various colloidal nanostructures such as Y3Fe5-xAlxO12-TRITC, γ-Fe2O3?Cs2Mo6Br14@SiO2 and γ-Fe2O3-QDs will be presented. At the outset, the first synthesis of aluminium substituted garnet Y3Fe5-xAlxO12 by the citrate gel process and its surface modification by TRITC through grafting of 3-aminopropyltrimethoxysilane (g-APS) for hyperthermia application will be reported. Secondly, the synthesis of nanoparticles under restricted environments offered by water-in-oil microemulsions provides excellent control over particle size and shape and interparticle spacing. These environments have been used in the synthesis of silica nanoparticles (50 nm) with a magnetic nanocrystalline core surrounded by optically active molybdenum atoms clusters. Finally, we will resume the preparation of composite magnetic-QD bioconjugable micelles by simultaneous encapsulation of hydrophobic CdSe/ZnS QDs (2-4 nm) and magnetic γ-Fe2O3 nanoparticles (3-4 nm) into water soluble micelles of synthetic functional PEG amphiphiles bearing a bioactivable terminal group.